Inexpensive Aerial Photogrammetry for Studies of Whales and Large Marine Animals - Dawson, Stephen M.; Bowman, M. Hamish; Leunissen, Eva; Sirguey, Pascal (Frontiers in Marine Science, 2017)
We describe a simple system enabling accurate measurement of swimming marine mammals and other large vertebrates from low-altitude single-frame photogrammetry via inexpensive modifications to a “prosumer” unmanned aerial vehicle (UAV) equipped with gimballed micro4/3 camera and 25 mm lens. Image scale is established via an independently powered LIDAR/GPS data-logging system recording altitude and GPS location at 1 Hz. Photogrammetric calibration of the camera and lens allowed distortion parameters to be rigorously accounted for during image analysis, via a custom-programmed Graphical User Interface running in MATLAB. The datalogger, camera calibration methods and measurement software are adaptable to a wide range of UAV platforms. Mean LIDAR accuracy, measured from 10 bridges 9-39 m above water, was 99.9%. We conducted 136 flights in New Zealand’s subantarctic Auckland Islands to measure southern right whales. Mean lengths of 10 individual whales, each photographed between 7 to 15 times, had CVs (SD/mean) ranging from 0.5-1.8 % (mean = 1.2 %). Repeated measurements of a floating reference target showed a mean error of c.1 %. Our system is relatively inexpensive, easily put together, produces accurate, repeatable measurements from single vertical images, and hence is applicable to a wide range of ecological questions in marine and terrestrial habitats.